Studies on the use of recombinant spider silk protein/polyvinyl alcohol electrospinning membrane as wound dressing - Zhao L (Dove Medical Press, 2017)
Liang Zhao,1,2,* Denglong Chen,2,3,* Qinghua Yao,2 Min Li2 1College of Life Sciences and Technology Xinxiang Medical University, Henan, 2College of Life Sciences, Fujian Normal University, Fuzhou, 3College of Environmental Science and Engineering, Fujian Normal University, Fuzhou, People’s Republic of China *These authors contributed equally to this work Abstract: A series of wound membranes of polyvinyl alcohol and recombinant spider silk protein (pNSR16) was prepared by electrospinning. The membrane was analyzed by scanning electron microscopy, atomic force microscopy, and Fourier transform infrared spectroscopy. The result showed that the three factors that affected average fiber diameter from high to low were, voltage, flow speed, and solidification distance; and the three factors that affected fiber uniformity from high to low were, flow speed, solidification distance, and voltage. The fibers adhered together after being dealt with alcohol. pNSR16 transformed from random coil into β-sheet after being immersed in alcohol. Additionally, the porosity of the electrospun membrane was 84.85%, which was higher than that of cast membrane prepared with the same composition. Experiments of applying electrospun membranes as wound dressing for Sprague Dawley rat wound healing showed that it could promote wound healing and basic fibroblast growth factor expression. Keywords: recombinant spider silk protein, polyvinyl alcohol, electrospinning, characterization, wound dressing